Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile. Issue 20 (18th October 2018) - Zhou, Xue-Ming; Zhang, Bin; Chen, Guang-Ying; Han, Chang-Ri; Jiang, Kun-Chi; Luo, Ming-Yue; Meng, Bo-Zheng; Li, Wen-Xin; Lin, Shi-Dai
Abstract: A new benzocoumarin derivative, dendrocoumarin (1 ), along with itolide A were isolated from the stems of Dendrobium nobile . The structure of the new compound1 elucidated on the basis of NMR and mass spectroscopic data. Compounds1 and2 showed broad spectrum antibacterial activity against five terrestrial pathogenic bacteria. Abstract :